Upregulation of endogenous thrombopoietin receptor (MPL) with in vivo passage of calreticulin (CALR) mutant Ba/F3 cells, highlighting MPL as the requisite cytokine receptor for CALR mediated transformation. (July 2019) - Brooks, Stefan A.; Kim, Daniel M.; Morse, Sarah J.; Nguyen, Quy H.; Craver, Brianna M.; Lai, Hew Yeng; Fleischman, Angela G.
Highlights: in vivo passage of calreticulin mutant Ba/F3 cells leads to cytokine independence. These cells expanding in mice have upregulation of endogenous MPL. MPL is the requisite cytokine receptor for calreticulin mediated transformation.